Locally biosynthesized gibberellins in Populus stems are involved in the regulation of wood development - Huili Su; Chunyang Wan; Xiaokang Fu; Jian Hu; Yuanxun Tao; Keming Luo; Changzheng Xu (Forestry Research)
Gibberellins (GAs) are a class of hormonal regulators, which influence various developmental processes in the life cycle of plants. In woody species, bioactive GAs, whose precursors are synthesized by the action of terpene cyclases and carried in the phloem by long-distance translocation from aerial shoot apex and leaves, are known to be a mobile signal to modulate stem growth. However, little is known about the existence and role of local GA synthesis in stems. Here we provide multiple lines of evidence suggesting the presence of local de novo GA biosynthesis in poplar stems and assess its role in wood development. First, the application of a GA biosynthetic inhibitor to decapitated poplar led to a significant reduction in local GA accumulation in the stem. Second, the correlated expression patterns of GA biosynthetic genes across radial tissues showed the existence of local GA production in the stem. Third, bioactive GA assays in transgenic poplar lines expressing Arabidopsis CPS, which encodes the first enzyme in the GA biosynthetic pathway, further confirmed the occurrence of local GA biosynthesis in the bark and cambial zones, but not in the xylem. Finally, modified local GA biosynthesis in the stem revealed its positive effects on secondary growth during wood formation. Taken together, our results demonstrate the existence of local de novo biosynthesis of GAs in poplar stems that contributes to the regulation of wood development via stimulating cambial activity.